Compact Design of 1x2 MIMO Microstrip Patch Antenna with Corners Trimmed for Vehicle-to-Vehicle Communication - Zaw, Ko Ko; Khin, Ei Ei; Oo, Thandar; Hla Myo Tun; Pradhan, Devasis (Journal of Novel Engineering Science and Technology, 2025)
This paper mainly focuses on the compact design of circularly polarized microstrip patch antenna for vehicle-to-vehicle communication. The charging time of electric vehicle is longer waiting time than compared to traditional gasoline-based vehicles. The charging is done at the public charging stations. When the vehicles need charging while driving, they communicate with Dedicated Short Range Communications (DSRC) band to send the information to the nearest vehicles and receive information from the charging station. Moreover, the DSRC band is used in many application areas such as Intelligent Transportation System (ITS), Electronic Toll Collection (ETC), Collision Avoidance, and connected vehicles. The vehicle-to-vehicle communication system needs to achieve higher data rates multimedia. These requirements cannot be supported by using single microstrip patch antenna. However, some research challenges have been in MIMO antenna such as antenna miniaturization, decoupling, and isolation between the antennas. The research solution for the problem statement in this study is emphasized on the corner trimmed is added in the rectangular patch and ground plane to make the current part longer and the impedance matching better, and to get low ECC. After that, the mutual coupling can be reduced by adding suitable separation between two radiating patches. S12 and S21 are less than -20dB from 5.81 GHz to 5.930 GHz. So, the proposed antenna design is very appropriate for car-to-car (5.85-5.925 GHZ) communication. The measurement result of the proposed antenna is valid because the desired values such as minimum S11 ≤ -10 dB, VSWR ≤ 2, and ECC < 0.3 are obtained for V2V communication in both simulation and measurement results.